Smart tendon actuated flexible actuator - Billah, Md. Masum; Khan, Md. Raisuddin (Hindawi Publishing Corporation, 2015)
We investigate the kinematic feasibility of a tendon-based flexible parallel platform actuator. Much of the research on tendon-driven Stewart platforms is devoted either to the completely restrained positioning mechanism (CRPM) or to one particular type of the incompletely restrained positioning mechanism (IRPM) where the external force is provided by the gravitational pull on the platform such as in cable-suspended Stewart platforms. An IRPM-based platform is proposed which uses the external force provided by a compliant member. The compliant central column allows the configuration to achieve DOFs with tendons. In particular, this investigation focuses on the angular deflection of the upper platform with respect to the lower platform. The application here is aimed at developing a linkable module that can be connected to one another so as to form a “snake robot” of sorts. Since locomotion takes precedence over positioning in this application, a 3-DOF Stewart platform is adopted. For an arbitrary angular displace of the end-effector, the corresponding length of each tendon can be determined through inverse kinematics. Mathematical singularities are investigated using the traditional analytical method of defining the Jacobian.